Pengaruh Disiplin Kerja dan Fasilitas Kerja terhadap Kinerja Pegawai pada Kantor BPBD Kabupaten Mamuju Tengah - Muhammad Yunus; Anwar Anwar; Zainal Ruma; Siti Hasbiah; Resky Amalia Hamka (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this study is to explain and analyze the influence of work discipline and work facilities on employee performance. The independent variables in this study were work discipline and work facilities. The dependent variable in this study is employee performance. The population in this study is 84 employees at the Central Mamuju Regency Regional Disaster Management Agency office, consisting of 12 ASN employees and 72 contract employees. The sample determination method used in this study is total sampling, which is a method of taking the entire population as a sample. The sample used in this study is a saturated sample, namely the entire population of 84 employees The analysis method used in this study is the multiple linear regression analysis method using Statistical Product And Service Solution (SPSS). The results of this study show that work discipline has a significant effect on employee performance and work facilities have a significant effect on employee performance and simultaneously work discipline and work facilities have a significant effect on employee performance.